Thomas Aquinas: on law, tyranny and resistance - N. P. Swartz (Acta Theologica)
Thomas Aquinas’s notion on law, tyranny and resistance served as a limitation on governmental powers. When those who bear the law command things which exceed the competence of such authority, the subject is free to obey or disobey. The function of the law culminates in two maxims: quantum ad vim coactivam legis and quantum ad vim directivam. With regard to the former, the prince is above the law (legibus solutus). It implies the principle of Salus reipublicae suprema lex, which means that the safety of the state is the supreme law. According to this principle property, liberty and life (basic individual rights) are subordinate to or even sacrificed for the supposed public good. With regard to the latter, the prince’s power should be subject to the law. The vis directiva limits the authority of the prince. This principle is in accordance with the rule of law. This notion is concomitant with the constitutional principles entrenched in the Constitution of South Africa, Act 108 of 1996. The idea of the Constitution is also bolstered by the entrenchment of the rule of law. The purpose of the rule of law is to protect basic individual rights. Hereafter the rule of law requires the prince or state to act in accordance with the law. It also means that the prince or branches of state must obey the law. If the prince or state acts without legal authority, it is acting lawlessly, which is against the notion of a constitutional democracy.